HIMACHAL PRADESH STATE ACTION PLAN ON CLIMATE CHANGE (SAPCC): A STUDY - Avantika (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Himachal Pradesh State Action Plan on Climate Change (SAPCC) is a significant step towards enhancing climate resilience in the Western Himalayas, one of India’s most vulnerable regions. This paper studies SAPCC Version I (2012), highlighting progress made in aligning the state-level climate action plan with national and international frameworks. The study highlights key sectoral reforms, a shift towards decentralised governance, and a greater focus on community participation, social adaptation and gender inclusiveness. Using social, economic and cultural context to understand these advancements, this paper demonstrates the transformative potential of SAPCC Version I. The plan adopts a visionary, data-driven approach to climate challenges, addresses critical socio-economic dimensions, improves institutional frameworks and lays the foundations for sustainable development. The article also identifies areas where there is potential for future action, including local implementation strategies, equitable financing, and gender-sensitive policies